Primary English Language Education Policy in Vietnam's Disadvantaged Areas: Implementation Barriers - Thi Thanh Tra Do; Maura Sellars; Thi Thuy Le (MDPI AG, 2022)
In the context of English as a global language, compulsory English language education at the primary level has become an inevitable trend in many non-English-speaking countries, including Vietnam. However, there have been concerns regarding how English language policy is realised across contextual settings, especially in rural and remote areas of Vietnam. Based on language-in-education goals, this article investigates English language policy implementation in Vietnam's rural and remote areas from the perspective of primary English teachers from 2008 onwards. The present paper employs a desk review of existing literature, policy analysis, and semi-structured interviews. Data collected from multiple sources show the inequality of access to English language learning in the rural localities. The findings also indicate a significant gap between the current English language policy goals and implementation in the rural primary sector regarding slow execution, curriculum variations, limited teaching resources, inappropriate pedagogy, and assessment. These problems have been accelerated due to a shortage of teachers as well as inconsistency and limitations related to pre-service teacher training programs and recruitment. Identifying significant challenges of English language policy implementation in the Northwest of Vietnam helps shed light on primary English education in remote and marginalised regions. Therefore, the recommendations target policy makers, teacher educators, and stakeholders to assist primary English teachers in rural areas to improve and advance the success of primary English education in Vietnam's remote areas and beyond the specific context to which it refers.